The Search for the Codex Cardona - Bauer, Arnold J. (Book collections on Project MUSE., 2009)
The Codex Cardona is a Mexican "painted book" which may date from the 16th century and has been assessed inconclusively by such places as Sotheby's, the Getty, and Stanford University. This book describes the author's quest to determine the ori.